The Infinite Retina : Spatial Computing, Augmented Reality, and how a collision of new technologies are bringing about the next tech revolution /: Spatial Computing, Augmented Reality, and how a collision of new technologies are bringing about the next tech revolution. (2020) - Cronin, Irena; Scoble, Robert
No abstract available